Modified Knottins as Potential Inhibitors of HCV NS3 Protease - Talanova, A.V.; Shcherbinin, D.S.; Kolesanova, E.F.; Veselovsky, A.V. (Biomedical Chemistry: Research and Methods, 2024)
Knottins form a group of peptides containing approximately 30 amino acid residues. Their structures are stabilized by three disulfide bonds forming a characteristic “pseudo-knotted” structure. Several modifications in knottin from Momordica cochinchinensis were made to convert it to inhibitor of human hepatitis C (HCV) NS3 protease. These modifications of the knottin template included deletion of several residues from the N-terminus, replacement of residues in- and outside the inhibitor loop and replacement of certain L-amino acids by their D-stereoisomers. Binding energy values for protein-knottin complexes were estimated by MM-GBSA methods. Two designed knottins showed high stability in knottin-protease HCV complexes and values of binding energy comparable with known peptide inhibitors from crystal structures.